2017
DOI: 10.18632/oncotarget.15862
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial treatment with polyI:C and anti-IL6 enhances apoptosis and suppresses metastasis of lung cancer cells

Abstract: Activation of TLR3 stimulates cancer cell apoptosis and triggers secretion of inflammatory cytokines. PolyI:C, a TLR3 agonist, activates immune cells and regresses metastatic lung cancer in vivo. Although polyI:C reportedly kills lung carcinomas, the mechanism remains elusive. Here, we demonstrated that polyI:C suppressed the proliferation and survival of metastatic (NCI-H358 and NCI-H292) and non-metastatic (A549) lung cancer cells. Notably, A549, NCI-H292 and NCI-H358 which are inducible by polyI:C, expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…A novel therapy would benefit from simultaneously targeting the IL-6 signaling pathway and stimulating the tumor microenvironment to promote antitumor immune responses via CD40. Lau et al (38) reported that a combination of an immune stimulator with IL-6 blockade increases apoptosis and decreases metastasis in a lung cancer model, and Caetano et al (39) have shown that IL-6 blockade inhibits progression of lung cancer and can change the tumor microenvironment toward an antitumor phenotype. In this article, we report the design of a novel oncolytic adenovirus, LOAd713, for the treatment of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A novel therapy would benefit from simultaneously targeting the IL-6 signaling pathway and stimulating the tumor microenvironment to promote antitumor immune responses via CD40. Lau et al (38) reported that a combination of an immune stimulator with IL-6 blockade increases apoptosis and decreases metastasis in a lung cancer model, and Caetano et al (39) have shown that IL-6 blockade inhibits progression of lung cancer and can change the tumor microenvironment toward an antitumor phenotype. In this article, we report the design of a novel oncolytic adenovirus, LOAd713, for the treatment of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In CTB assays, the LSD value in A549, H292, H1299, and H358 are 3.222, 2.969, 3.423, and 3.396, respectively. Figure 1B and previously in [3]. For each time point, cell counts were normalized with corresponding DMSO vehicle (or PBS) -treated controls.…”
Section: Hiltonol +++ Suppressed Lung Cancer Cell Proliferation Throumentioning
confidence: 92%
“…PolyI:C (polyinosinic-polycytidilic acid) has been shown to suppress the proliferation and survival of lung cancer cells [3]. Hiltonol (also known as poly-ICLC) is an advanced polyI:C synthetic RNA designed by stabilizing polyI:C with poly-lysine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also indicated that cancer cells in the liver or those that metastasise to the lungs can be killed and eliminated from the liver by a specific subset of liver NK cells [8][9][10]. NK cells are capable of secreting inflammatory cytokines that can result in Th1 cell activation, and it is this ability that is reported to be responsible for their antitumour activity [11,12].…”
Section: Introductionmentioning
confidence: 99%